Analysis of Student’s Critical Thinking Skills In Solving High Order thinking Skill (HOTS) Problems On Atomic Structure Material - yanti denia; Maefa Eka Haryani (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
21century education demands mastery of critical thinking skills as part of higher order thinking abilities. The Merdeka Curriculum was introduced to address these demands however, students’ critical thinking skills in solving Higher Order Thinking Skills (HOTS) problems have not yet been comprehensively measured. This study aims to analyze students’ critical thinking skills in solving HOTS problems on atomic structure topics. This research employed a mixed-methods approach with a QUAN-Qual design. Data were collected through HOTS based cognitive tests and interviews. The analysis of critical thinking skills was based on Facione’s indicators, including interpretation, analysis, evaluation, and inference. The results showed that students’ critical thinking skills reached 62% (good) for interpretation, 61% (good) for analysis, 59% (moderate) for evaluation, and 64% (good) for inference. These findings indicate that students’ critical thinking skills are generally at a good level; however, improvement is still needed, particularly in the evaluation aspect, through more innovative and HOTS-oriented learning approaches.